Nondestructive examination of fuel channels in PHWR nuclear power plants. (14th November 2006) - Savin, A.; Udpa, L.; Steigmann, R.; Grimberg, R.; , S. Udpa
This paper proposes the use of a new type of eddy current transducer – the inner eddy current transducer with rotating magnetic field. This transducer has the capability to detect the discontinuities of pressure tubes and also the presence and concentration of Zirconium hydrides. This method is very promising for the determination and characterisation of blisters and delayed hydride cracking. By inversion of data, it is possible to estimate the depth and equivalent diameter of blisters.